The lost abbey of Eynsham - Parrinder, Steve (Archaeopress Publishing Ltd., 2019)
Eynsham was one of the few religious foundations in England in continuous use from the late Saxon period to the Dissolution. This book aims to rescue this important abbey from obscurity by summarising its history and examining its material remains, most of which have never been published before.